Accounting map / Khairiah Ahmad Nur Farahah Ahmad Pauzi … [et al.] - Ahmad, Khairiah; Ahmad Pauzi, Nur Farahah; Karim, Mohd Syazwan; Roslan, Nurfarahin; Shamsudin, Adriana; Syed Ibrahim, Sharifah Norhafiza (Division of Research and Industry Linkages, 2017)
Accounting is important to us in dealing with our daily life. It helps us to plan and manage financial matters more effectively. However, many perceive accounting as a very difficult subject due to its technical difficulties. This perception is very common particularly to the non-accounting students. That is why this 'Accounting Map' is designed. It aims to assist non-accounting students and others to better grasp and understand basic financial accounting and reporting concepts and principles. This map provides a handy overview of the whole accounting system as it illustrates and links the processes of accounting cycle, starting from classifying transactions into orderly and meaningful categories, recording the transactions into appropriate journals, posting to the correct ledgers, extracting the Trial Balance and the preparation of Financial Statements; the Statement of Profit or Loss and the Statement of Financial Position. This map summarizes the whole accounting processes which are conventionally explained and illustrated separately and by stages in the textbook. 'Accounting Map’ benefits not only to students but also useful for teachers or lecturers. It serves as an extra teaching tool to motivate and enrich students’ interest towards accounting subject and to finally excel in acquiring not only accounting concepts but also its practical application.